2022
DOI: 10.3390/app12147105
|View full text |Cite
|
Sign up to set email alerts
|

Study on Accuracy of CFD Simulations of Wind Environment around High-Rise Buildings: A Comparative Study of k-ε Turbulence Models Based on Polyhedral Meshes and Wind Tunnel Experiments

Abstract: It is important to create a comfortable wind environment around high-rise buildings for outdoor activities. To predict the wind environment, Computational Fluid Dynamics (CFD) has been widely used by designers and engineers. However, the simulation results of different CFD turbulence models might significantly vary. This paper researched the wind environment around a typical high-rise building and verified the accuracy of the CFD simulations based on polyhedral meshes. The differences between the simulation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…However, tetrahedral cells have limitations in excessive stretching, leading to increased element counts compared to structured grids. Polyhedral cells offer a solution by reducing cell count, improving grid quality, and enhancing calculation accuracy. Hosseini et al extensively studied the effect of cell type on total mesh cell counts, mesh quality, simulation time, accuracy of prediction, and residuals. They found that the cell type plays a crucial role in prediction accuracy for coarse meshes, whereas the cell type effect can be ignored for fine meshes.…”
Section: Cfd Modelmentioning
confidence: 99%
“…However, tetrahedral cells have limitations in excessive stretching, leading to increased element counts compared to structured grids. Polyhedral cells offer a solution by reducing cell count, improving grid quality, and enhancing calculation accuracy. Hosseini et al extensively studied the effect of cell type on total mesh cell counts, mesh quality, simulation time, accuracy of prediction, and residuals. They found that the cell type plays a crucial role in prediction accuracy for coarse meshes, whereas the cell type effect can be ignored for fine meshes.…”
Section: Cfd Modelmentioning
confidence: 99%
“…Therefore, the turbulent condition is applied under the realizable k-ε turbulence model for the present study. This model is selected as it provides more accuracy and less computational time [31,32]. The governing equations of the heat transfer and turbulent flow for the fluid can be seen in the following equations [31,32].…”
Section: Spray and Turbulent Modelsmentioning
confidence: 99%
“…This model is selected as it provides more accuracy and less computational time [31,32]. The governing equations of the heat transfer and turbulent flow for the fluid can be seen in the following equations [31,32]. Continuity:…”
Section: Spray and Turbulent Modelsmentioning
confidence: 99%
“…The convergence residuals for velocity, momentum, and turbulence kinetic energy should be set to be below 10−4. However, if the convergence of the continuity equation is poor, the criterion can be relaxed to 10−3 [43,45]. Based on Soligo's findings on comfort wind speed and frequency under different conditions [46], as well as the research by Murakami et al, which introduced the outdoor comfort wind range under different temperature ranges [47], it has been determined that the comfortable wind speed for the Lingnan region in summer is 0.7-5.0 m/s.…”
Section: Mapping Of Ventilation Conditionsmentioning
confidence: 99%